Correction to: Neural networks for estimation of facial palsy after vestibular schwannoma surgery (Journal of Clinical Monitoring and Computing, (2023), 37, 2, (575-583), 10.1007/s10877-022-00928-9) - Rampp, Stefan; Holze, Magdalena; Scheller, Christian; Strauss, Christian; Prell, Julian (Journal of Clinical Monitoring and Computing, 2023)
In this article the title was incorrectly given as “Original Research” instead research Neural networks for estimation of facial palsy after vestibular schwannoma surgery’ but should have been ‘Neural networks for estimation of facial palsy after vestibular schwannoma surgery’. The original article has been corrected.
CRIS-Team Scopus Importer:2023-06-02